The Wisdom of The Bayan Indigenous Community in Conserving The Traditional Forest in North Lombok, Indonesia - Aan Firdaus Tramdheni; I Wayan Suana; Kurniasih Sukenti (Jurnal Biologi Tropis, 2023)
Local wisdom is formed as a process of interaction between humans and their environment to meet their various needs. The Bayan indigenous people are a community that until now still adheres to the beliefs and customs of their ancestors. The purpose of this study was to determine the forms of local wisdom that exist in indigenous peoples in protecting customary forests in Bayan Village, North Lombok. As well as to find out the efforts of indigenous peoples to maintain and maintain local wisdom in protecting customary forests in Bayan Village, North Lombok Regency Collecting data using participatory observation and interviews. Based on the results of the study, it can be seen that the Bayan indigenous people at present tend to be sectoral, meaning that traditional implementation activities are local (village). The success of customary forest development cannot be separated because it is supported by local wisdom which is always obeyed. In an effort to preserve the customary forest area, it is protected by a local policy called awiq-awiq.